The evolution of school league tables in England 1992–2016: 'Contextual value‐added', 'expected progress' and 'progress 8'. (25th January 2017) - Leckie, George; Goldstein, Harvey
Abstract : Since 1992, the UK Government has published so‐called 'school league tables' summarising the average General Certificate of Secondary Education (GCSE) 'attainment' and 'progress' made by pupils in each state‐funded secondary school in England. While the headline measure of school attainment has remained the percentage of pupils achieving five or more good GCSEs, the headline measure of school progress has changed from 'value‐added' (2002–2005) to 'contextual value‐added' (2006–2010) to 'expected progress' (2011–2015) to 'progress 8' (2016–). This paper charts this evolution with a critical eye. First, we describe the headline measures of school progress. Second, we question the Government's justifications for scrapping contextual value‐added. Third, we argue that the current expected progress measure suffers from fundamental design flaws. Fourth, we examine the stability of school rankings across contextual value‐added and expected progress. Fifth, we discuss the extent to which progress 8 will address the weaknesses of expected progress. We conclude that all these progress measures and school league tables more generally should be viewed with far more scepticism and interpreted far more cautiously than they have often been to date.